Hardware-in-the-loop simulation for automatic rack and pinion steering system - Mohammad Nasir, Mohd Zakaria; Dwijotomo, Abdurahman; Abdullah, Mohd Azman; Hassan, Muhammad Zahir; Hudha, Khisbullah (Trans Tech Publications Inc, 2012)
As new features for driver assistance and active safety system are going rapidly in vehicle, the interface between hardware and simulation model within a virtual and real environment has become necessity. In this paper, a Hardware-in-the-loop Simulations (HILS) test rig has been develop using actual rack and pinion steering mechanism with controller in Matlab xPC Target environment, LVDT and rotary encoder sensors installed for data measurement at various steering angle. It can manipulate the steering mechanism with various control structure, decrease time with real experiment and trial risk as well as improve development efficiency. Results from HILS experimental model demonstrate a linear pattern occurred from maximum lock-to-lock steering wheel angle with acceptable error.